(untitled) (Research, Society and Development, 2021)
COVID-19 has become a high-risk issue of global concern. The glycoprotein (S) peak in the virion envelope is proteolytically cleaved into the S1 and S2 subunits, and receptor recognition is mediated by receptor binding domain (RBD) and membrane fusion. This is a literature review of a qualitative nature based on scientific production from studies published between 2019 and 2021 that addressed the main objective of this study to correlate DPP4 in SARS-CoV-2 infection. Coronavirus tropism mainly depends on the ability of the glycoprotein (S) entry peak to bind to cell surface receptors. It is currently reported that SARS-CoV-2 can use angiotensin-2 converting enzyme (ACE2), the same receptor as SARS-CoV, to infect humans. However, recent evidence suggests that SARS-CoV-2 binds to DPP4/CD26 after entering airway cells. It appears that the interaction between the peak glycoprotein SARS-CoV-2 and human DPP4/CD26 (also known as dipeptidyl peptidase-4 (DPP4) is a key factor in sequestration and virulence. In the absence of results from well-designed randomized clinical trials, the efficacy or safety data of DPP4 inhibitors in the treatment of COVID-19 must be interpreted with caution and no clear conclusions can be drawn.The results of these studies may help reveal the impact of using drugs that inhibit DPP4 and whether they can be effective in the treatment of COVID-19 infection.